An oxygen bridge coupled three-dimensional array NiFeCo-LDH / MXene hetero-composite material, a preparation method and application thereof

CN122907618APending Publication Date: 2026-10-13XINYU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611130332.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

针对现有MXene/LDH复合材料存在的纳米片无序堆叠、界面结合力弱及传输动力学缓慢等问题,本发明通过构建垂直生长的三维阵列结构以提供开放的离子扩散通道,并利用原位生长策略在异质界面处构筑稳固的氧桥键合以增强电子耦合效应与结构稳定性,从而显著提升材料的电化学性能及长循环寿命

Benefits of technology

[0017]本发明提供的一种氧桥耦合三维阵列NiFeCo-LDH/MXene异质复合材料及其制备方法和应用,与现有技术相比,具有以下显著优点:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907618A_ABST
    Figure CN122907618A_ABST
Patent Text Reader

Abstract

The application discloses an oxygen bridge coupled three-dimensional array NiFeCo-LDH / MXene hetero-composite material and a preparation method and application thereof, and belongs to the technical field of new energy storage materials. x The material is Ti3C2T x MXene is a conductive substrate, a three-dimensional array NiFeCo-LDH nanostructure is constructed through in-situ growth, and a Ti-O-M (M=Ni, Fe, Co) oxygen bridge bond is formed at the interface. The application utilizes a cationic surfactant to regulate the interface charge distribution and combines the complexation and slow-release effect, realizes directional nucleation and ordered growth of active components. The obtained composite material has excellent conductivity, rich redox active sites and open transmission channels, and significantly improves the electron transmission efficiency and ion diffusion rate. The material preparation method is simple and has good repeatability, and can be used as an electrode material of a lithium ion battery, a sodium ion battery and a supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy storage materials and electrochemical technology, specifically relating to a method for constructing NiFeCo-LDH / MXene heterostructures with oxygen bridging bonds through surfactant-induced directional growth of heterostructures, and its application in energy storage devices such as lithium-ion batteries, sodium-ion batteries, and supercapacitors. Background Technology

[0002] With the rapid development of portable electronic devices, electric vehicles, and large-scale energy storage systems, the market is placing higher demands on novel energy storage devices that combine high energy density, long cycle life, and excellent rate performance. Lithium-ion and sodium-ion batteries, due to their high operating voltage, high energy density, and long cycle life, have become some of the most promising electrochemical energy storage technologies. However, traditional electrode materials generally suffer from limited electron transport rates, slow ion diffusion kinetics, and insufficient structural stability during cycling, which severely restricts their further development.

[0003] Layered double hydroxides (LDHs) have attracted widespread attention due to their abundant redox active sites, tunable layered structure, and high theoretical specific capacity. However, LDHs materials themselves have poor conductivity and are prone to aggregation and structural collapse during charge and discharge, leading to reduced utilization of active sites and decreased cycle stability.

[0004] Two-dimensional transition metal carbides / nitrides (MXenes) possess excellent electronic conductivity, abundant surface functional groups, and large interlayer spacing, making them ideal carriers for high-performance composite electrode materials. Existing research typically employs in-situ growth or physical mixing methods to combine LDHs with MXenes to improve the conductivity and structural stability of the composites. However, existing MXene / LDH composite systems still have the following shortcomings: (1) Structural disorder: The nucleation and growth process of LDH nanosheets on the MXene surface is difficult to control effectively, and they are prone to forming disordered stacked structures, which leads to tortuous electron and ion transport paths and limits rate performance. (2) Weak interface coupling: MXene and LDHs are mostly bonded by direct physical contact or weak interface interaction, lacking strong chemical bonding (such as oxygen bridge bond), resulting in low interface charge transport efficiency and easy interface peeling under high rate or long cycle. (3) Discontinuous pore structure: The internal pore structure of the composite material is not continuous, and the electrolyte is difficult to fully wet the hydrophobic MXene surface, resulting in low utilization of active sites, especially under high loading.

[0005] Therefore, there is an urgent need to develop a novel LDHs / MXene heterocomposite material that can achieve directional nucleation and ordered array growth of MXene on the surface and strengthen interfacial oxygen bridging coupling, so as to fundamentally solve the above-mentioned structural and interface problems, thereby significantly improving the electron transport efficiency, ion diffusion kinetics and cycle stability of electrode materials. Summary of the Invention

[0006] The purpose of this invention is to provide an oxygen-bridged coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, its preparation method, and its applications. Addressing the problems of disordered nanosheet stacking, weak interfacial bonding, and slow transport kinetics in existing MXene / LDH composite materials, this invention constructs a vertically grown three-dimensional array structure to provide open ion diffusion channels, and utilizes an in-situ growth strategy to build stable oxygen bridge bonds at the heterojunction interface to enhance electronic coupling and structural stability, thereby significantly improving the material's electrochemical performance and long cycle life.

[0007] This invention provides an oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, with Ti3C2T x MXene serves as the conductive substrate, and NiFeCo layered bimetallic hydroxide (NiFeCo-LDH) is grown in situ on the Ti3C2T substrate. x A three-dimensional array structure is formed on the surface of MXene; the NiFeCo layered bimetallic hydroxide and the Ti3C2T x MXenes are connected by at least one oxygen bridge bond selected from Ti-O-Ni, Ti-O-Fe, and Ti-O-Co.

[0008] Preferably, the NiFeCo layered bimetallic hydroxide accounts for 70% to 80% of the mass percentage in the heterogeneous composite material.

[0009] Preferably, in the NiFeCo layered bimetallic hydroxide, the molar ratio of Ni, Fe and Co elements is (1~4):(1~2):(1~2).

[0010] Preferably, the Ti3C2T x The surface functional groups of MXene include one or more of -O, -OH and -F.

[0011] Preferably, the three-dimensional array structure is a nanosheet array with an array height of 50~1000nm and an array spacing of 10~500nm.

[0012] This invention also provides a method for preparing the above-mentioned oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, comprising the following steps: (1) Ti3C2T x MXene aqueous dispersion was added to N,N-dimethylformamide and stirred to obtain a uniform dispersion. (2) Add cationic surfactant and ascorbic acid to the dispersion, and after dissolution, add nickel salt, iron salt, cobalt salt and urea to form a precursor solution; (3) The precursor solution is placed in a hydrothermal reactor for hydrothermal reaction; (4) The product is washed and dried to obtain the heterogeneous composite material.

[0013] Preferably, in step (2), the cationic surfactant is hexadecyltrimethylammonium bromide (CTAB), and the amount added is 100~300mg; the amount added of ascorbic acid is 500~1500mg.

[0014] Preferably, in step (1), the volume of N,N-dimethylformamide is 30~60 ml; in step (3), the temperature of the hydrothermal reaction is 100~140℃ and the time is 8~16 h.

[0015] Preferably, the nickel salt, iron salt, and cobalt salt are selected from NiCl2·6H2O, FeCl3·6H2O, and CoCl2·6H2O, respectively.

[0016] This invention also provides the application of the above-mentioned oxygen-bridge coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material in lithium-ion battery anode materials.

[0017] The present invention provides an oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, its preparation method, and its application, which have the following significant advantages compared with the prior art: 1. A dual high-speed electron / ion transport channel based on oxygen bridging bonds was constructed; this invention achieves high-speed electron / ion transport in two-dimensional Ti3C2T through strong interface modulation. x An ordered, vertically grown ternary NiFeCo-LDH nanosheet array was constructed in situ on the MXene surface. Unlike simple physical contact, the stable Ti-O-Ni, Ti-O-Fe, and Ti-O-Co oxygen bridges formed at the heterojunction act as high-speed channels for electron migration, effectively overcoming the bottleneck of poor conductivity in traditional hydroxides. At the same time, the continuous three-dimensional open channels significantly reduce the electrolyte wetting resistance, enabling rapid and coordinated electron and ion transport and endowing the material with excellent rate performance.

[0018] 2. A dual synergistic preparation strategy of "surface charge regulation + complexation-based sustained release" is proposed. Addressing the challenge of disordered stacking of LDH nanosheets, this invention utilizes the cationic surfactant CTAB to alter the surface charge distribution of MXene, inducing directional nucleation of metal ions. Combined with the weak binding effect of ascorbic acid (LAA), the release rate of metal ions is controlled. This mechanism enables the one-step hydrothermal method to prepare high-quality composite materials without the need for high-temperature solid-state sintering. The process is simple and the raw material cost is low, making it highly potential for large-scale production.

[0019] 3. Precise tunability of microstructure and electrochemical performance is achieved; this material system exhibits extremely high tunability. By precisely adjusting the Ni / Fe / Co feed ratio, the amount of additives (CTAB / LAA), and the reaction temperature and time parameters, the thickness of the nanosheets, the array height, and the density of interfacial oxygen bridges can be precisely customized. This allows the technology platform to flexibly adapt to the performance requirements of different devices such as lithium-ion batteries, sodium-ion batteries, or supercapacitors.

[0020] 4. This invention solves the problems of volume expansion and active material shedding during cycling at the atomic scale. Existing physically composite materials have weak interfacial bonding and are prone to failure due to volume expansion during long-term cycling. This invention firmly "anchors" the array structure to the conductive substrate through oxygen bridging bonds, constructing a highly elastic three-dimensional framework that can strictly control the structural volume expansion rate during charging and discharging within 10-15%. This robust structural design significantly simplifies the cumbersome protective modification steps and significantly improves the stability of long-cycle electrode materials.

[0021] 5. Exhibiting excellent electrochemical stability and promising prospects for industrial application; as an energy storage anode material, this oxygen-bridged coupled heterocomposite material exhibits extremely high capacity retention and significantly reduced charge transfer impedance in long-term charge-discharge tests. Its advantages in suppressing volume expansion and improving cycle life make it highly valuable for applications in new energy vehicle power batteries and large-scale grid energy storage. Attached Figure Description

[0022] Figure 1 This is the XRD pattern of the NiFeCo-LDH / MXene heterocomposite material provided in this application; Figure 2 These are TEM images and elemental mappings of the NiFeCo-LDH / MXene heterocomposite material provided in this application. Figure 3 This is the nitrogen adsorption-desorption isotherm of the NiFeCo-LDH / MXene heterocomposite material provided in this application; Figure 4 These are SEM images of the NiFeCo-LDH / MXene heterocomposite materials provided in this application; Figure 5 These are the cyclic voltammetry (CV) curves of the NiFeCo-LDH / MXene heterocomposite material provided in this application; Figure 6 This is a test diagram of the lithium storage cycle performance of the NiFeCo-LDH / MXene heterocomposite material provided in this application; Figure 7 This is a test diagram of the sodium storage cycle performance of the NiFeCo-LDH / MXene heterocomposite material provided in this application. Detailed Implementation

[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0024] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0025] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0026] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0027] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0028] The first aspect of this invention provides an oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, wherein the material is based on Ti3C2T xMXene is used as a conductive substrate, and NiFeCo layered bimetallic hydroxide is grown in situ on Ti3C2T. x A three-dimensional array structure is formed on the MXene surface. NiFeCo layered bimetallic hydroxide and Ti3C2T x MXenes are connected by at least one oxygen bridge bond selected from Ti-O-Ni, Ti-O-Fe, and Ti-O-Co.

[0029] The three-dimensional array structure design utilizes the high conductivity of MXene and the high pseudocapacitance of LDH. More importantly, the NiFeCo layered bimetallic hydroxide and the Ti3C2T x MXenes are connected by at least one oxygen bridge bond among Ti-O-Ni, Ti-O-Fe and Ti-O-Co. This strong chemical bond (oxygen bridge coupling) not only solves the problem of high contact resistance at traditional physical mixing interfaces, but also creates a high-speed channel for electron migration across the interface, which significantly improves the rate performance and cycle stability of the material.

[0030] Regarding the composition and microstructure of the material, the NiFeCo layered bimetallic hydroxide accounts for 70%–80% by mass in the heterocomposite material, with the balance being MXene. This ratio ensures that the material has sufficient active material to provide capacity while retaining sufficient conductive framework support.

[0031] In the NiFeCo layered bimetallic hydroxide, the molar ratio of Ni, Fe, and Co is (1~4):(1~2):(1~2), preferably 2:1:1. The synergistic effect of the three metal elements further optimizes the electronic structure and improves the intrinsic conductivity. Ti3C2T x The surface functional groups of MXene include one or more of -O, -OH, and -F. These abundant surface functional groups not only serve as reaction sites for forming the aforementioned "oxygen bridges," but also contribute to electrolyte wetting.

[0032] The three-dimensional array structure is a nanosheet array with an array height of 50–1000 nm (preferably 100–800 nm) and an array spacing of 10–500 nm (preferably 50–300 nm). This open three-dimensional channel structure greatly increases the specific surface area and provides excellent mechanical and lattice expansion buffer space, fundamentally preventing electrical contact deactivation of the active phase during frequent ion insertion / extraction processes.

[0033] The second aspect of this invention provides a method for preparing the aforementioned oxygen-bridged coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material. This method employs a "one-step hydrothermal method combining interfacial charge regulation and complexation-controlled release," aiming to achieve directional growth and strong chemical bonding of active materials on a conductive substrate through precise control of reaction kinetics. Specific preparation steps and key technical parameters are as follows: Step (1): Dispersion preparation and solvent stripping; Ti3C2T x The MXene aqueous dispersion was added to the organic solvent N,N-dimethylformamide (DMF) and a uniform and stable dispersion was obtained under magnetic stirring.

[0034] Parameter range: The volume of DMF is controlled between 30 and 60 mL, preferably 50 mL. Ti3C2T x The concentration of MXene dispersion was 1-3 mg / mL, and the ultrasonic dispersion time was 1 h. The polar organic solvent DMF was introduced to replace some water molecules, effectively weakening the van der Waals forces between MXene sheets and preventing irreversible restacking. This process significantly increased the specific surface area of ​​MXene, exposing more surface functional groups (-O, -OH, -F), providing abundant active sites and sufficient adhesion space for subsequent in-situ growth of LDH.

[0035] Step (2): Interfacial charge regulation and precursor construction: The cationic surfactant hexadecyltrimethylammonium bromide (CTAB), ascorbic acid (LAA), and precursor metal salts and urea from nickel, iron and cobalt sources are added sequentially to the above dispersion and stirred thoroughly to obtain a homogeneous precursor solution.

[0036] Specifically, the amount of CTAB added is 100-300 mg, preferably 200 mg; it is added at a mass ratio of CTAB to MXene of 2:5, and the magnetic stirring time is 30 min at room temperature. The amount of LAA added is 50-150 mg, preferably 100 mg; The precursor metal salts for nickel, iron, and cobalt sources are chloride or nitrate salts, wherein the molar ratio of Ni, Fe, and Co is (1~4):(1~2):(1~2), preferably 2:1:1, and the mixture is magnetically stirred at room temperature for 30 min.

[0037] This step is the core of constructing heterogeneous interfaces: 1. Electrostatic Adsorption Induction: As a cationic surfactant, CTAB is directionally adsorbed onto the negatively charged MXene surface through electrostatic interactions, forming a positively charged modification layer. This "interfacial charge regulation" not only improves the dispersibility of MXene but also acts as a "soft template" to induce the negatively charged LDH precursor to align perpendicularly to the substrate surface, preventing its disordered accumulation.

[0038] 2. Complexation-based sustained-release rate control: As a multidentate ligand, LAA can form stable complexes with metal ions. In the initial stage of the reaction, it locks in some metal ions, reducing the concentration of free metal ions, thereby inhibiting the homogeneous explosive nucleation of LDH in solution and forcing the nucleation reaction to mainly occur at the active sites on the MXene surface (i.e., "in-situ nucleation").

[0039] Step (3): In-situ growth and oxygen bridging (hydrothermal reaction); The precursor solution is transferred to a high-pressure reactor and subjected to a one-step hydrothermal reaction at a preset temperature. The slow-release effect of LAA is used to control the directional nucleation and vertical interweaving growth of metal ions at the active sites of oxygen-containing functional groups on the charge-regulated MXene surface, and in-situ self-assembly and coupling are used to form a three-dimensional array heterostructure with strong interfacial oxygen bridging bonds; Specifically, the reaction temperature is 100~140 ℃, preferably 120 ℃; the reaction time is 8~16 h, preferably 12 h. Within this temperature range, urea slowly hydrolyzes to continuously provide OH⁻, which, combined with the thermal decomposition of LAA to release metal ions, synergistically controls the crystal growth rate.

[0040] As the crystal grows perpendicularly along the c-axis, the oxygen / hydroxyl groups in the LDH lattice undergo dehydration condensation reactions with the titanium atoms on the MXene surface, forming stable Ti-O-Ni, Ti-O-Fe, or Ti-O-Co oxygen bridges in situ. This strong chemical bonding constructs a "highway" for electron migration across the interface, significantly reducing contact resistance. Simultaneously, the resulting 50–1000 nm high three-dimensional nanosheet array structure not only shortens the ion diffusion path but also effectively buffers volume expansion during charge and discharge, significantly improving the material's rate performance and cycle life.

[0041] Step (4): Washing, drying and electrode application; After the reaction is completed, the furnace is cooled and the crude product is washed with deionized water and anhydrous ethanol alternately by centrifugation until neutral, and then freeze-dried to obtain pure oxygen bridge coupled ternary LDH / MXene heterocomposite material.

[0042] The freeze-drying temperature was controlled between -50 ℃ and -60 ℃, and the time was 24~48 h. Low-temperature freeze-drying utilizes the principle of water sublimation, avoiding the agglomeration and collapse of nanosheets caused by capillary forces during traditional oven drying, thus completely preserving the loose, porous three-dimensional array morphology of the material. The resulting composite material can be directly used as an energy storage active material (such as a supercapacitor or battery anode). When mixed with a conductive agent and binder at a mass ratio of 8:1:1 for slurry coating, it exhibits excellent electrochemical performance.

[0043] A third aspect of this invention provides the application of the aforementioned material; the composite material can be directly used as the active material of an energy storage electrode. It is mixed and ground with a conductive agent and a binder in a predetermined ratio (e.g., a mass ratio of 8:1:1) in an organic solvent to form a uniform electrode slurry, which is then uniformly coated onto the surface of a current collector. After vacuum drying and stamping, an energy storage electrode sheet is obtained. This electrode can be used as a negative electrode for lithium-ion batteries, sodium-ion batteries, or supercapacitors, exhibiting excellent rate performance and long cycle life.

[0044] Unless otherwise specified, "room temperature" in this invention refers to 20-30°C; all raw materials and chemical reagents used in this invention are commercially available.

[0045] Example 1

[0046] This embodiment provides an oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, its preparation method, and its application.

[0047] In the composite material prepared in this embodiment, the mass percentage of NiFeCo-LDH is 80 wt%, and the mass percentage of Ti3C2T is [missing information]. x The mass percentage of MXene is 25 wt%. This composite material exhibits an open three-dimensional sheet-like array heterogeneous morphology, with NiFeCo-LDH nanosheets vertically and in situ bonded to the MXene surface. The interface is covalently coupled by stable Ti-OM (M=Ni, Fe, Co) oxygen bridge bonds. This strong chemical bonding effectively reduces the interfacial charge transport impedance and enhances the structural stability of the material.

[0048] The preparation steps of this oxygen-bridged coupled ternary LDH / MXene heterocomposite material are as follows: Step (1): Ti3C2T x MXene aqueous solution was dispersed in N,N-dimethylformamide (DMF) to prepare a uniform dispersion with a concentration of 2 mg / mL. The volume of DMF was controlled at 50 mL, and the ultrasonic dispersion time was 1 h.

[0049] Step (2): Add solid hexadecyltrimethylammonium bromide (CTAB) and solid ascorbic acid (LAA) to the dispersion. The amount of CTAB added is 200 mg, and the mass ratio of CTAB to MXene is 2:5. Stir continuously magnetically at room temperature for 30 min. The amount of LAA added is 100 mg to fully regulate the surface charge of MXene. Add nickel chloride hexahydrate, ferric chloride hexahydrate, cobalt chloride hexahydrate (Ni:Fe:Co molar ratio of 2:1:1) and urea to the system in sequence, and stir magnetically at room temperature for 30 min.

[0050] Step (3): The precursor solution was transferred to a polytetrafluoroethylene substrate pressurized reactor and sealed. It was then placed in a constant temperature oven at 120 °C for an in-situ one-step hydrothermal reaction for 12 h.

[0051] Step (4): After the reaction is completed, the product is naturally cooled to room temperature. The precipitated product is taken out and washed repeatedly by centrifugation with deionized water and anhydrous ethanol for more than 5 times until the pH of the supernatant is close to neutral. The washed wet product is placed in a freeze dryer and vacuum freeze-dried at -55 ℃ for 36 h to obtain pure oxygen bridge coupled ternary LDH / MXene heterocomposite material.

[0052] This embodiment also provides steps for preparing energy storage electrode sheets and assembling batteries using the above-mentioned heterogeneous composite materials: Electrode slurry preparation and coating: Take 80 mg of the oxygen-bridged coupled ternary LDH / MXene heterocomposite material prepared above, 10 mg of conductive agent acetylene black, and 10 mg of binder polyvinylidene fluoride (PVDF), and add an appropriate amount of N-methylpyrrolidone (NMP) as a solvent. Grind thoroughly in an agate mortar for 30 min, mix evenly, transfer to a test tube bottle and stir magnetically for 4 h to obtain an electrode slurry with uniform viscosity. Coat the slurry evenly onto a carbon-coated aluminum foil current collector using a scraper, then transfer it to a vacuum drying oven and vacuum dry at 50 ℃ for 12 h. Cut and punch into circular energy storage positive / negative electrode sheets with a diameter of 13 mm using a punching machine.

[0053] Lithium half-cell assembly: Button half-cells were assembled in an argon glove box with water and oxygen content both below 0.1 ppm. A circular electrode sheet was used as the working electrode, a pure lithium metal sheet as the counter / negative electrode, and Celgard 2400 as the separator. A CR2032 button half-cell was assembled using a solution of 1.0 M LiPF6 dissolved in DMC+EC+EMC (volume ratio 1:1:1) with common additives.

[0054] Sodium test half-cell assembly: A circular electrode sheet is used as the working electrode, a pure metallic sodium sheet is used as the counter / negative electrode, high-purity glass fiber is used as the separator, and a 1.0 M NaPF6 solution dissolved in EC+DEC (volume ratio 1:1) is used as the electrolyte to assemble a CR2032 button half-cell.

[0055] Electrochemical testing: Using a battery testing system, constant current charge-discharge (GCD) cycle life and coulombic efficiency are tested at a specified current density; cyclic voltammetry (CV) behavior is tested using an electrochemical workstation.

[0056] Example 2

[0057] This embodiment provides a method for preparing an oxygen-bridge coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, the main difference being that the cationic surfactant CTAB is not added in step (2).

[0058] Step (1): Ti3C2T x MXene aqueous solution was dispersed in N,N-dimethylformamide (DMF) to prepare a uniform dispersion with a concentration of 3 mg / mL. The volume of DMF was controlled at 60 mL, and the ultrasonic dispersion time was 1 h.

[0059] Step (2): Add solid hexadecyltrimethylammonium bromide (CTAB) and solid ascorbic acid (LAA) to the dispersion. The amount of LAA added is 100 mg to fully regulate the surface charge of MXene. Add nickel chloride hexahydrate, ferric chloride hexahydrate, cobalt chloride hexahydrate (Ni:Fe:Co molar ratio of 2:1:1) and urea to the system in sequence, and stir magnetically at room temperature for 30 min.

[0060] Step (3): The precursor solution was transferred to a polytetrafluoroethylene substrate pressurized reactor and sealed. It was then placed in a constant temperature oven at 140 °C for an in-situ one-step hydrothermal reaction for 8 hours.

[0061] Step (4): After the reaction is completed, the product is naturally cooled to room temperature. The precipitated product is taken out and washed repeatedly by centrifugation with deionized water and anhydrous ethanol for more than 5 times until the pH of the supernatant is close to neutral. The washed wet product is placed in a freeze dryer and vacuum freeze-dried at -60 ℃ for 24 h to obtain pure oxygen bridge coupled ternary LDH / MXene heterocomposite material.

[0062] Example 3

[0063] This embodiment provides a method for preparing an oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, the preparation method is as follows: Step (1): Ti3C2T x MXene aqueous solution was dispersed in N,N-dimethylformamide (DMF) to prepare a uniform dispersion with a concentration of 1 mg / mL. The volume of DMF was controlled at 30 mL, and the ultrasonic dispersion time was 1 h.

[0064] Step (2): Add solid hexadecyltrimethylammonium bromide (CTAB) and solid ascorbic acid (LAA) to the dispersion. The amount of CTAB added is 300 mg, and the mass ratio of CTAB to MXene is 2:5. Stir continuously magnetically at room temperature for 30 min. The amount of LAA added is 100 mg to fully regulate the surface charge of MXene. Add nickel chloride hexahydrate, ferric chloride hexahydrate, cobalt chloride hexahydrate (Ni:Fe:Co molar ratio of 2:1:1) and urea to the system in sequence, and stir magnetically at room temperature for 30 min.

[0065] Step (3): The precursor solution was transferred to a polytetrafluoroethylene substrate pressurized reactor and sealed. It was then placed in a constant temperature oven and subjected to an in-situ one-step hydrothermal reaction at 100 °C for 8 h.

[0066] Step (4): After the reaction is completed, the product is naturally cooled to room temperature. The precipitated product is taken out and washed repeatedly by centrifugation with deionized water and anhydrous ethanol for more than 5 times until the pH of the supernatant is close to neutral. The washed wet product is placed in a freeze dryer and vacuum freeze-dried at -50 ℃ for 48 h to obtain pure oxygen bridge coupled ternary LDH / MXene heterocomposite material.

[0067] Example 4

[0068] This embodiment provides a method for preparing an oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material, the preparation method is as follows: Step (1): Ti3C2T x MXene aqueous solution was dispersed in N,N-dimethylformamide (DMF) to prepare a uniform dispersion with a concentration of 1 mg / mL. The volume of DMF was controlled at 30 mL, and the ultrasonic dispersion time was 1 h.

[0069] Step (2): Add solid hexadecyltrimethylammonium bromide (CTAB) and solid ascorbic acid (LAA) to the dispersion. The amount of CTAB added is 100 mg, and the mass ratio of CTAB to MXene is 2:5. Stir continuously magnetically at room temperature for 30 min. The amount of LAA added is 100 mg to fully regulate the surface charge of MXene. Add nickel chloride hexahydrate, ferric chloride hexahydrate, cobalt chloride hexahydrate (Ni:Fe:Co molar ratio of 2:1:1) and urea to the system in sequence, and stir magnetically at room temperature for 30 min.

[0070] Step (3): The precursor solution was transferred to a polytetrafluoroethylene substrate pressurized reactor and sealed. It was then placed in a constant temperature oven at 140 °C for an in-situ one-step hydrothermal reaction for 8 h.

[0071] Step (4): After the reaction is completed, the product is naturally cooled to room temperature. The precipitated product is taken out and washed repeatedly by centrifugation with deionized water and anhydrous ethanol for more than 5 times until the pH of the supernatant is close to neutral. The washed wet product is placed in a freeze dryer and vacuum freeze-dried at -55 ℃ for 36 h to obtain pure oxygen bridge coupled ternary LDH / MXene heterocomposite material.

[0072] Comparative Example 1 This comparative example provides a pure ternary NiFeCo-LDH material (without introducing an MXene substrate and charge modulation strategy).

[0073] The preparation method is as follows: without adding Ti3C2Tx MXene, nickel chloride hexahydrate, ferric chloride hexahydrate, cobalt chloride hexahydrate (molar ratio 2:1:1), ascorbic acid LAA, CTAB and urea are directly dissolved in deionized water, magnetically stirred for 30 min, and then transferred to a reaction vessel for hydrothermal reaction at 120 ℃ for 12 h. After the reaction is completed, pure NiFeCo-LDH solid is obtained by the same washing and freeze-drying treatment.

[0074] Following the electrode and battery assembly steps in Example 1, a comparative electrode sheet was prepared using pure NiFeCo-LDH as the active material, and lithium-storage and sodium-storage button half-cells were assembled and subjected to the same performance tests.

[0075] Effect verification and experimental analysis Effect verification and experimental analysis Example 1: Phase crystal structure analysis (XRD) X-ray diffraction (XRD) was performed on the oxygen-bridged ternary LDH / MXene heterocomposite material prepared in Example 1 to analyze its phase characteristics. The spectral results are as follows: Figure 1 As shown.

[0076] Depend on Figure 1 The results show that the prepared composite product exhibits clear and sharp characteristic diffraction peaks at 10.9°, 23.5°, 34.4°, 38.4°, and 60.8°, which strictly correspond to the (003), (006), (012), (015), and (113) crystal planes of the hexagonal layered bimetallic hydroxide (NiFe-LDH, JCPDS standard card number: 40-0215), respectively. This strongly indicates that the transition metal cobalt (Co) has been successfully doped into the main lattice of LDH without inducing any phase separation or impurity crystal transformation. At the same time, the (002) characteristic diffraction peak belonging to the two-dimensional transition metal carbide Ti3C2TxMXene can be clearly observed near a low angle of 5.8°. The entire spectrum has a stable baseline and extremely high purity, with no other chemical impurity peaks generated, confirming the pure crystalline phase of the heterogeneous coexistence of highly crystalline ternary NiFeCo-LDH and Ti3C2Tx MXene.

[0077] Example 2: Microscopic morphology and spatial distribution analysis of components (TEM / STEM-Mapping) The microstructure of the sample from Example 1 was characterized using transmission electron microscopy (TEM) and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) elemental mapping. The results are as follows: Figure 2 As shown.

[0078] From low-magnification TEM image ( Figure 2 a and Figure 2 e) It can be clearly observed that ultrathin ternary NiFeCo-LDH nanosheets with highly porous characteristics are grown in situ on the surface and edges of a two-dimensional Ti3C2TxMXene conductive substrate with extremely high areal density and high order, successfully constructing an open three-dimensional sheet-like array heterostructure with a continuous transport network. This non-tiling outward growth mode can significantly prevent the overlap and curling of MXene nanosheets during subsequent drying or charge-discharge processes, maximizing the exposure of high-density electrochemical active sites. Figure 2 The corresponding dark-field HAADF-STEM element mapping clearly shows that Ti (derived from the substrate) is concentrated in the core region of the central framework, while Ni, Fe, Co, and O exhibit a highly uniform, synchronous, and completely overlapping spatial distribution, extending throughout the entire three-dimensional external nanosheet array. This irrefutably confirms at the microscopic scale that the ternary NiFeCo-LDH has successfully achieved highly homogeneous in-situ integration at the molecular level.

[0079] Example 3: Quantitative Analysis of Specific Surface Area and Porous Network (BET) The micropore advantage of the sample from Example 1 was quantitatively audited using nitrogen adsorption-desorption tests (BET model and BJH method), and the results are as follows: Figure 3 As shown.

[0080] Figure 3 The nitrogen isotherm adsorption-desorption curves of this heterocomposite material are presented. According to the IUPAC classification, the curves exhibit distinct Type IV isotherm characteristics. At low relative pressures (P / P0 < 0.4), the adsorption amount increases gradually, indicating the presence of a certain microporous structure within the material. However, in the medium-to-high relative pressure range (P / P0 = 0.45–1.0), a significant H3-type hysteresis loop appears on the curves, a typical characteristic of slit-like mesoporous / macroporous networks formed by the disordered stacking of two-dimensional sheet-like materials. Calculations using the BET model show that the specific surface area of ​​this three-dimensional array composite material reaches 111.06 m² / g. Compared to conventional self-stacking LDH or pure MXene materials, its specific surface area is significantly improved.

[0081] Example 4: Analysis of the influence of different process conditions on the microstructure of NiFeCo-LDH / MXene composite (SEM) To verify the effects of different hydrothermal reaction temperatures and surfactants on the microstructure of the composite materials, the surface morphology of Examples 1, 2, 3, and 4, as well as the pure LDH sample, was characterized by scanning electron microscopy (SEM). The results are as follows: Figure 4 As shown in af.

[0082] (1) Optimal conditions - 120℃ hydrothermal (Example 1): such as Figure 4 As shown in ab, the sample prepared by hydrothermal reaction at 120 °C exhibits an ideal three-dimensional array heterostructure. It can be clearly observed that ultrathin NiFeCo-LDH nanosheets, approximately 500 nm in size, are vertically crosslinked and in situ loaded onto the surface of MXene two-dimensional nanosheets with extremely high areal density, high order, and uniformity. This interconnected, open three-dimensional network structure not only effectively prevents the stacking of MXene sheets but also exposes abundant electrochemical active sites, providing a structural basis for excellent rate performance.

[0083] (2) Pure phase aggregation—pure NiFeCo-LDH: such as Figure 4 As shown in Figure c, the pure NiFeCo-LDH sample without the introduction of the MXene conductive substrate exhibits a distinct hydrangea-like microstructure. Due to the lack of induced heterogeneous nucleation and spatial confinement effects from the two-dimensional sheet substrate, the NiFeCo-LDH nanosheets undergo severe disordered self-stacking and aggregation, resulting in a significant decrease in the material's specific surface area and the exposure of active sites.

[0084] (3) Low temperature conditions - 105℃ hydrothermal (Example 5): such as Figure 4 As shown in Figure d, when the hydrothermal reaction temperature was reduced to 105℃, the obtained sample failed to exhibit a typical, continuous three-dimensional array morphology. The reaction system could not overcome the crystallization activation energy barrier required for the directional epitaxial growth of NiFeCo-LDH along the MXene surface, causing the crystal to remain only at the initial nucleation stage and fail to develop a regular nanosheet array structure.

[0085] (4) High temperature conditions - 130℃ hydrothermal (Example 6): such as Figure 4 As shown in Figure e, when the hydrothermal reaction temperature is increased to 130℃, NiFeCo-LDH nanosheets can still maintain an array-like loading on the MXene surface. However, compared with the sample at 120℃, the lateral size of the nanosheets is significantly increased, and the sheet thickness is also greatly improved. This indicates that excessively high hydrothermal temperatures accelerate the crystal growth kinetics, leading to excessive grain growth, which is not conducive to the construction of ultrathin nanosheet arrays.

[0086] (5) Surfactant conditions—120℃ but with CTAB added: like Figure 4 As shown in f, when the hydrothermal reaction was maintained at 120 °C but the cationic surfactant CTAB was added (or when the preparation process parameters deviated from the optimal setting), the morphology of the composite product was significantly degraded. The figure only shows a relatively thick, disordered NiFeCo-LDH nanosheet / nanorobar structure, failing to achieve uniform distribution and ordered loading on the MXene surface. This indicates that the interfacial charge induction between the surfactant and the metal precursor must be in an optimal synergistic ratio (as in Example 1); once this synergistic balance is broken, LDH will undergo homogeneous nucleation and preferential growth in solution, thereby weakening its interfacial coupling with the MXene conductive substrate.

[0087] In summary, the results show that the hydrothermal reaction temperature and the synergistic ratio of surfactants are the decisive factors in regulating the morphology of NiFeCo-LDH on MXene surfaces. The optimal hydrothermal temperature (120 °C) and an appropriate CTAB-induced interfacial charge regulation strategy can effectively reduce the epitaxial growth energy barrier and induce the formation of a uniform, densely distributed, and strongly interfacially bonded ultrathin three-dimensional vertical array structure of NiFeCo-LDH. Conversely, excessively low or high temperatures, as well as imbalances in the surfactant ratio, will disrupt the formation of this array structure and hinder subsequent electrochemical performance.

[0088] Example 5: Electrochemical Peak Behavior Analysis by Single-Scan Cyclic Voltammetry (CV) Cyclic voltammetry (CV) tests were performed on the button half-cell assembled in Example 1 at a specific scan rate to analyze its electrochemical Faraday redox behavior. The curves are shown below. Figure 5 As shown.

[0089] Depend on Figure 5 It can be seen that the cyclic voltammetry (CV) curves of the oxygen-bridged coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material prepared in the embodiments of the present invention are shown at a specific scan rate. From the CV reaction behavior, it can be seen that the heterocomposite material exhibits a pair of sharp, significant, and well-symmetrical redox peaks within the charge-discharge scan voltage window. During charging (anodic voltage scan), the anodic oxidation peak near 1.3V corresponds to the oxidation of multivalent transition metal elements (Ni, Fe, Co) in the electrode active phase from low to high valence states, accompanied by ion intercalation / deintercalation. During discharging (cathode voltage scan), a corresponding cathode reduction peak is observed near 0.7V, corresponding to the reversible reduction reaction occurring at the transition metal center (transition from high to low valence states, accompanied by ion intercalation). This set of redox peaks exhibits high peak current density and sharp response, indicating that the active sites in the ternary layered bimetallic hydroxide are fully exposed and utilized. More importantly, the potential difference between the oxidation and reduction peaks remains at a low level. This indicates that the atomic-level cross-interface electron transport network constructed by interfacial oxygen bridges (Ti-OM) significantly reduces the charge transfer impedance of the heterostructure, enabling the system to maintain an extremely fast kinetic response rate during Faraday redox reactions involving multiple electron transfers.

[0090] Example 6: Long-lasting secondary lithium and sodium storage cycle durability verification (GCD) The button half-cells of Example 1 and Comparative Example 1 were placed in a constant current charge-discharge test system for long-cycle life comparison, and the lithium storage long-cycle performance was as follows: Figure 6 As shown, the sodium storage long-cycle performance is as follows: Figure 6 As shown.

[0091] Lithium battery long cycle test ( Figure 6The oxygen-bridged coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material prepared in this invention was tested using constant current charge-discharge tests to verify its long-term cycle life and coulombic efficiency in lithium-ion batteries. The performance curves of the heterocomposite material after 150 cycles at a high current density of 0.5 A / g are shown. As can be seen from the figure, after the initial activation cycles, the electrode exhibits extremely high and stable discharge specific capacity, maintaining a specific capacity of 810 mAh / g after 150 cycles with minimal capacity decay, demonstrating satisfactory cycle stability. More importantly, during the 150 electrochemical cycles, the coulombic efficiency of this electrode material rapidly increased and remained strictly maintained between 99.5% and 100%. In contrast, the pure NiFeCo-LDH in Comparative Example 1, due to the lack of a conductive substrate and severe self-stabilization, showed significantly worse charge-discharge specific capacity and cycle stability at the same current density.

[0092] Sodium long-cycle test ( Figure 7 To further verify the structural tolerance and long-term sodium storage stability of the oxygen-bridged coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material prepared in this invention during the insertion / extraction of large-radius ions, this composite material was assembled into a sodium-ion half-cell as the active material, and subjected to deep constant-current charge-discharge long-cycle testing at a high current density of 0.5 A / g. The figure shows the long-cycle lifetime and coulombic efficiency curves of the electrode in the sodium storage test. Experimental results show that after 900 cycles, the specific capacity remained at 308 mAh / g, with no significant capacity decay, and the capacity curve exhibited an excellent stable trend. Furthermore, except for a slightly lower coulombic efficiency in the first cycle due to the formation of the solid electrolyte interphase (SEI) film, from subsequent cycles onwards, the coulombic efficiency of the electrode rapidly increased and remained strictly stable within the extremely high efficiency range of 99.8% to 100.2%.

[0093] The two sets of long-cycle stability test results constitute a perfect closed loop of evidence, thoroughly confirming the core mechanism advantage of the present invention: the atomically scaled in-situ Ti-OM strong oxygen bridge bond has ultra-high mechanical and electrochemical bonding energy, which fundamentally prevents the problem of "delamination and peeling" that is very easy to occur in the active phase of traditional physical composite materials under repeated large volume expansion stress (especially sodium storage process), and ensures long-term electrical contact integrity.

[0094] Those skilled in the art can make various modifications and applications without departing from the essential characteristics of the embodiments. For example, each component detailed in the embodiments can be modified and operated, and the differences associated with such modifications and applications can be considered to be included within the scope of protection of the invention as defined in the appended claims.

[0095] The embodiments described in this specification are intended to imply that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment of the invention. These terms appearing throughout the specification do not necessarily refer to the same embodiment. Furthermore, when a particular feature, structure, or characteristic is described in connection with any embodiment, it is assumed that it falls within the scope of those particular features, structures, or characteristics that could be implemented by one of ordinary skill in the art in conjunction with other embodiments.

Claims

1. A three-dimensional array NiFeCo-LDH / MXene heterocomposite material coupled with oxygen bridges, characterized in that, With Ti3C2T x MXene serves as the conductive substrate, and NiFeCo layered bimetallic hydroxide is grown in situ on the Ti3C2T substrate. x A three-dimensional array structure is formed on the MXene surface; The NiFeCo layered bimetallic hydroxide and the Ti3C2T x MXenes are connected by at least one oxygen bridge bond selected from Ti-O-Ni, Ti-O-Fe, and Ti-O-Co.

2. The oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material according to claim 1, characterized in that, The NiFeCo layered bimetallic hydroxide accounts for 70% to 80% of the mass percentage in the heterogeneous composite material.

3. The oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material according to claim 1, characterized in that, In the NiFeCo layered bimetallic hydroxide, the molar ratio of Ni, Fe and Co elements is (1~4):(1~2):(1~2).

4. The oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material according to claim 1, characterized in that, The Ti3C2T x The surface functional groups of MXene include one or more of -O, -OH and -F.

5. The oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material according to claim 1, characterized in that, The three-dimensional array structure is a nanosheet array with an array height of 50~1000 nm and an array spacing of 10~500 nm.

6. A method for preparing an oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Ti3C2T x MXene aqueous dispersion was added to N,N-dimethylformamide and stirred to obtain a uniform dispersion; (2) Add cationic surfactant and ascorbic acid to the dispersion, and after dissolution, add nickel salt, iron salt, cobalt salt and urea to form a precursor solution; (3) The precursor solution is placed in a hydrothermal reactor for hydrothermal reaction; (4) The product is washed and dried to obtain the heterogeneous composite material.

7. The preparation method according to claim 6, characterized in that, In step (2), the cationic surfactant is hexadecyltrimethylammonium bromide, and the amount added is 100~300 mg; the amount added of ascorbic acid is 500~1500 mg.

8. The preparation method according to claim 6, characterized in that, In step (1), the volume of N,N-dimethylformamide is 30~60 ml; in step (3), the temperature of the hydrothermal reaction is 100~140℃ and the time is 8~16 h.

9. The preparation method according to claim 6, characterized in that, The nickel salt, iron salt, and cobalt salt are selected from NiCl2·6H2O, FeCl3·6H2O, and CoCl2·6H2O, respectively.

10. The application of the oxygen-bridge-coupled three-dimensional array NiFeCo-LDH / MXene heterocomposite material as described in any one of claims 1 to 5 in lithium-ion battery anode materials.